An Analysis of Digital Technology Adoption and Its Impact on College Students’ Purchase Intentions for Cultural and Creative Products in Guangxi, China - Qifang, Qiu; Thongma, Watcharanan; Inthurit, Danaikrit; Sitthikun, Suthira (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
With the rapid development of mobile internet, e-commerce, and digital platforms, the digital economy has profoundly reshaped the cultural consumption landscape. Focusing on college students in Guangxi, China, this study empirically examines how digital technology adoption influences their purchase intention toward cultural and creative products (CCPs). Drawing on the Technology Acceptance Model (TAM), Innovation Diffusion Theory (IDT), and Cultural Identity Theory, a quantitative survey was conducted, yielding 389 valid responses. Data were analyzed using descriptive statistics and multiple regression analysis. The results indicate that perceived ease of use, facilitating conditions, hedonic motivation (from TAM/UTAUT2), perceived compatibility, observability (from IDT), and cultural knowledge (from Cultural Identity Theory) significantly and positively affect students' purchase intention. The model explains 21.5% of the variance in purchase intention. By integrating technological, innovative, and cultural-psychological factors into a unified framework, this study provides theoretical insights and practical implications for universities, cultural enterprises, and policymakers seeking to promote sustainable development of the cultural and creative industry in the digital economy era.